Interpreting Hegel's phenomenology of spirit expositions and critique of contemporary readings - Boldyrev, Ivan A. 1984-; Stein, Sebastian 1980- (Routledge, 2022)
"This book focuses on the interpretations of Hegel's Phenomenology of Spirit that have proven influential over the past decades. Current readers of Hegel's Phenomenology face an abundance of interpretive literature devoted to this difficult text and confront a plethora of different philosophical presuppositions, research strategies and hermeneutic efforts.To enable better orientation within the interpretative landscape, the essays in this volume summarize, contextualize and critically comment on the issues and currents in contemporary Phenomenology scholarship. There is a common set of three questions that each of the contributions seeks to answer: (1) What kind of text is the Phenomenology of Spirit? (2) What do the different strategies of interpretation conceptually bring to the text? (3) How do different interpreters justify their verdict on whether the Phenomenology is still a viable project?
Includes bibliographical references and index
Keywords: Hegel, Georg Wilhelm Friedrich -- 1770-1831 -- Die Phänomenologie des Geistes; Hegel, Georg Wilhelm Friedrich / 1770-1831 / Phänomenologie des Geistes; Spirit; Consciousness; Truth; Phänomenologie des Geistes (Hegel, Georg Wilhelm Friedrich); Aufsatzsammlung